Autologous, allogeneic tumor cells or genetically engineered cells as cancer vaccine against melanoma - Schadendorf, Dirk; Paschen, Annette; Sun, Yuansheng (Immunology letters, 2000)
Melanoma is a prototype of immunogenic tumor to which various types of immunotherapy have been applied extensively over the past decades. Melanoma vaccines are designed for the purpose of immune modulation and subsequent anti-tumor effects in the process of an active specific immunotherapy. Previous attempts of these vaccines include immunization with whole tumor cells/cell lysates admixed with nonspecific adjuvants. While these vaccines generated enhanced anti-tumor immunity in a subset of patients, some of which showing prolonged survival compared to historical controls, no clinical benefit has so far been demonstrated in a properly controlled phase III study. New-generation melanoma vaccines, which are based on genetic modifications of tumor cells to express cytokines, generated long-lasting systemic anti-tumor immunity in animal models. Translation of these preclinical results primarily into melanoma patients with advanced diseases, shows the potential of these vaccines to induce systemic anti-tumor immune responses and in some instances tumor regression with acceptably low toxicity. Higher efficacy of this novel vaccine approach would be expected when used in a postsurgical adjuvant setting when the tumor load is small. Also other novel vaccine approaches such as dendritic cell-based therapy hold promise for the treatment of melanoma. But the clinical value of all these new approaches has to be analysed in prospectively randomized clinical studies.